SISTEM STERILISASI AIR MINUM ISI ULANG PADA DEPOT AIR MINUM ISI ULANG (DAMIU) DI KOTA DAN KABUPATEN PEKALONGAN - Nila Oktaviani; Siska Rusmalina (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
In this time, most society have the solid activity, so that society tend to to chosen the way of more practical with the expense which cheaper relative in fulfilling amount of water required drink the nya  that  is  by  using  drinking  water  refill (Sulityandari,  2009). Water consumed  shall  fulfill  the good water quality, for that observation to irrigate refill to utilize to protect consumer. Research to know  whether  system  of  sterilization  of  drinking  water  refill  (DAMIU)  in  Town  and  Regency Pekalongan yield the water which with quality and competent to be consumed.Research diskriptif to see the system of sterilization of drinking  water refill ( DAMIU) in Town and Pekalongan Regency yield the water which with quality and can be consumed by conducting test of cemaran of bacterium Colioform. Sampel Research use 37 DAMIU which is gone the round of Town and Regency Pekalongan enlisted by and also not yet been enlisted in DINKES Town and or Regency Pekalongan.Result of research region of subdistrict Wiradesa 5 from 12 sampel give the impure result which are  positive  by  bacterium  Colioform.  Result  of  test  DAMIU  region  of  subdistrict  of  North Pekalongan  5  from  13  impure  sampel  by  bacterium Colioform.  Result  of  test  DAMIU  region  of subdistrict  of  East  Pekalongan  6  from  12  impure  sampel by  bacterium Colioform.  All  DAMIU which  used  as  sampel  have  opened  enlisted  Public  Health  Service  of  Pekalongan  town  and  also regency and a Quality inspection irrigate.Keywords: Sterilization system, town or Bat regency.